HUBUNGAN PENGETAHUAN TENTANG SANITASI HIGIENE DENGAN SIKAP PENJAMAH MAKANAN DI KAWASAN KULINER TAMAN JAJAN - Nur Alissa Leonita Husaini; Ms Mariani; Guspri Devi Artanti (Jurnal Socia Akademika, 2022)
This study aims to identify the relationship between knowledge about hygiene sanitation and the attitudes of food handlers related to food management in the Culinary Area of Taman Jajan. This research uses a quantitative approach with survey methods and a cross-sectional approach. This research was conducted in the culinary area of Taman Jajan. The sample of this study was 62 food handlers and used the purposive sampling method. This study showed that as many as 51 respondents (82.26%) had a piece of knowledge about hygiene sanitation with a suitable category. As many as 54 respondents (87.1%) had attitudes related to food management with good categories. There is a positive and significant relationship between the variables of knowledge about hygiene sanitation and the variable attitudes of food handlers related to food management in the Culinary Area of Taman Jajan. As many as 15.2% of food handlers' attitudes related to food management were determined by their knowledge of hygiene and sanitation. As many as 84.8% were determined by other variables not studied in this study. Advice to the manager of the Taman Jajan culinary area to provide a briefing of practical hygiene sanitation knowledge in the form of pamphlets or brochures to food handlers